"C" Trouble: Class IC Anti-arrhythmic Toxicity - Maia Eng#; William Wung#; Uma N Srivatsa#; Gagan D Singh (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
The most common cardiac arrhythmia encountered in clinical practice is atrial fibrillation (AFib). AFib has significant effects on long-term mortality and stroke, and contributes greatly to overall healthcare costs, affects quality of life and the functional status of many patients [1]. The incidence and prevalence of AFib continues to rise with age, when comorbidities that affect rhythm management frequently coexist [1]. Due to improved quality of life, rhythm control is a common treatment strategy [2,3]. This is accomplished with the use of antiarrhythmic agents across the Singh-Vaughn- Williams classification [4]. In patients with structurally normal hearts, Class IC agents such as flecainide and propafenone are commonly prescribed for maintenance of sinus rhythm as the first line therapy [5]. Despite their prevalent use, the relative toxicities of these agents are infrequent, and therefore seldom emphasized in the most recent guidelines and reviews [4]. The lack of survival benefit from rhythm management strategy 0utilizing antiarrhythmic drugs have been suggested to be due to adverse effects from these agents [6]. The mechanism of action is on the cellular action potential and can be proarrhythmic due to the lack of specificity on the atrial tissue. It is critical that clinicians be able to recognize the causes, signs and symptoms of toxicity from these antiarrhythmic agents.